Fintech in Islamic Finance Theory and Practice - Umar A. Oseni, S. Nazim Ali (2019)
Featuring high-level analysis of Islamic law, this book examines fintech in Islamic finance from both theoretical and empirical perspectives. Whilst building on existing approaches, it also discusses the current application of fintech in promoting financial inclusion through innovative solutions in Muslim-majority countries, identifying future directions for policy-makers.